The effect of defibrotide on reendothelialisation in microarterial anastomosis - (:unkn) unknown (Turkish Neurosurgical Society, 1994)
Endothelial injury during microarterial anastomosis typically results in mural thrombus formation. However, endothelial cells produce various substances which suppress thrombus formation and maintain normal vascular wall architecture by preventing muscular proliferation. Therefore, in order to reduce the risk of thrombus formation following microarterial anastomoses, drugs which stimulate endothelial cells and active reendothelialization might be beneficial. Using a rat model, we studied the effect of defibrotide on reendothelialization following microarterial anastomosis and concluded that defibrotide is an effective agent which supports reendothelialization and decreases the incidence of posanastomotic thrombi.